Decision Support System (SPK) for Selection of New Student Admissions and Majors Using Simple Additive Weigthing (SAW) and Fuzzy Tsukomoto at SMA Negeri 1 Kalirejo - Sulastri, Sulastri (PT Mattawang Mediatama Solution, 2022)
Decision support system (DSS) is an information system that helps managers with unique strategic decisions (non-recurring) or a system that provides a means that allows managers to develop information so that it is appropriate to support the decisions they will make. In this study, the SAW method was used to select student admissions and the Fuzzy Tsukamoto method was used to specialize students. This research is to select and organize specializations so that the school can easily select students and students are not wrong in organizing specializations. The results of the student selection test using the SAW method selected 281 students from 325 students who registered and by using the Fuzzy Tsukamoto method there were 19 students who were wrong in determining the majors of the 281 selected students.